Attribute-Level Performance, Satisfaction, and Behavioral Intentions over Time: A Consumption-System Approach - Mittal, Vikas; Kumar, Pankaj; Tsiros, Michael (Journal of Marketing, 1999)
Instead of offering products or services alone, increasingly, firms and their partners are offering consumption systems. Consumption systems are offerings characterized by a significant product and service subsystem, as well as a pattern of consumption in which consumption occurs in multiple episodes over time. The authors develop a theoretical model for conceptualizing satisfaction with consumption systems and empirically test it using longitudinal data from 5206 automobile owners. Results show that an intertemporal examination of attribute-level performance, satisfaction, and behavioral intentions can improve an understanding of their relationships because these relationships change as the consumption of the product unfolds. For example, on the basis of their salience, attribute weights in determining satisfaction shift over time. Furthermore, the crossover effect of product and service satisfaction in determining intentions toward the manufacturer and the service provider is asymmetric, and this asymmetry reverses over time. Service satisfaction initially has a much larger impact in determining intentions toward the manufacturer, but later, product satisfaction is more influential in generating intentions toward the service provider and manufacturer. The results show that there is no direct link between satisfaction and behavioral intentions. Rather, satisfaction affects behavioral intentions in the future through a dual-mediation route.